Stemness-driven clusters in ovarian cancer: immune characteristics and prognostic implications - Xinyan Zeng; Xinyan Zeng; Wentian Wu; Xiaoqin Li; Xiaoqin Li; Xiaorui Wu; Xiaorui Wu; Yingying Du; Ping Li; Ping Li; Ping Li (Frontiers in Oncology)
BackgroundOvarian cancer (OC) is the most common malignant gynecological tumor. Cancer cells with high stemness often exhibit resistance to anti-tumor therapies, contributing to recurrence and poor prognosis. However, stemness-related subtypes in OC and their therapeutic implications remain underexplored.MethodsWe identified stemness-associated genes by comparing transcriptome profiles between adherent and sphere-forming SKOV3 cells. Unsupervised clustering was applied to define stemness-related molecular subgroups in OC patients. A prognostic model was constructed using WGCNA and LASSO regression, and a nomogram was developed by integrating clinicopathological variables. Differences in the tumor microenvironment (TME), tumor mutation burden (TMB), immune checkpoint expression, and drug sensitivities were evaluated between risk groups. Single-cell RNA sequencing was used to investigate stemness-related cell types. Functional assays were conducted to validate the role of AKAP12 in OC progression.ResultsThree distinct stemness-related subgroups were identified with significant differences in prognosis and immunological features. Fibroblasts were identified as major contributors to the maintenance of stemness traits in the TME. AKAP12 was found to be positively associated with stemness phenotypes. Knockdown of AKAP12 reduced tumor sphere formation, impaired cell migration, and enhanced cisplatin sensitivity. Immunohistochemistry in clinical samples and OC organoids confirmed the correlation between AKAP12 and the immune checkpoint molecule OX40L.ConclusionThis study establishes a novel stemness-related gene signature for prognosis prediction and therapeutic stratification in OC. AKAP12 was identified as a potential biomarker and therapeutic target, offering new avenues for precision treatment in stemness-driven OC.